Facile Formation of Stable Neutral Radicals and Cations from [22]Smaragdyrin BF2 Complexes. Issue 11 (12th January 2023) - Deng, Weikang; Liu, Yang; Shimizu, Daiki; Tanaka, Takayuki; Nakai, Akito; Rao, Yutao; Xu, Ling; Zhou, Mingbo; Osuka, Atsuhiro; Song, Jianxin
Abstract: meso ‐Trimesityl‐substituted [20]smaragdyrin freebase was synthesized by p ‐toluenesulfonic acid catalyzed reaction of 5‐mesityldipyrromethane and 2, 14‐dibromodipyrrin in an improved yield of 63 %. Unexpectedly, treatment of the [20]smaragdyrin freebase with BF3 ⋅ OEt2 and triethylamine (TEA) gave a stable radical species, in which the BF2 unit is coordinated at the tripyrrin site, probably by ready release of a hydrogen atom of a [22]smaragdyrin BF2 complex. Similar treatment of [22]smaragdyrin free base produced another [22]smaragdyrin BF2 complex, in which the BF2 unit is coordinated at the dipyrrin site. The tripyrrin site coordinated neutral radical was oxidized with AgSbF6 to give a stable antiaromatic cation; this was reduced with NaBH4 to its 22π congener, which was easily oxidized back to the neutral radical in the air and rearranged to thermodynamically stable dipyrrin site coordinated [22]smaragdyrin BF2 complex upon treatment with BF3 ⋅ OEt2 and TEA. Further, the dipyrrin site coordinated [22]smaragdyrin BF2 complex was similarly oxidized to a stable neutral radical and a stable cation in a stepwise manner. This work demonstrates a rare ability of smaragdyrin BF2 complexes to exist in multiple redox states, particularly forming a stable neutral radical by facile release of a hydrogen atom. Abstract : meso ‐Trimesityl‐substituted [20]smaragdyrin was synthesized in 63 % yield by TsOH‐catalyzed reaction of 5‐mesityldipyrromethane and 2, 14‐dibromotripyrrin. Treatment of [22]smaragdyrin BF2 complex with BF3 ⋅ OEt2 and TEA gave a stable neutral radical, which was oxidized to stable [20]smaragdyrin antiaromatic cationwith AgSbF6 . Reduction of the neutral radical with NaBH4 gave aromatic [22]smaragdyrin BF2 complex, which was readily oxidized to the neutral radical and converted to thermodynamically stable [22]smaragdyrin BF2 complex upon treatment with BF3 ⋅ OEt2 and TEA. Similarly, [22]smaragdyrin BF2 complex was oxidized to stable neutral radical and antiaromatic cation in a stepwise manner. As such, smaragdyrin BF2 complexes have been shown to be very intriguing, allowing for various electronic states including stable radicals and cations.